PELAKSANAAN PEMBELAJARAN MEMBATIK DALAM KEGIATAN EKSTRAKURIKULER SISWA SEKOLAH MENENGAH PERTAMA NEGERI 10 PADANG - Yogi Aria Sastra; Ramalis Hakim (Universitas Negeri Padang, 2020)
This Research aimed to find in the process of batik work in SMP Negeri 10 Padang by Extracurricular, supporting and hampering factors in realization it and the result of batik work by students. The type of this research is qualitative descriptive with observation, interview, and documentations. Data analysis techniques via data reduction, presentation, and verification. The Result showed that realization of batik work is smooth, supporting factors are fund enough and facilitated by school all of needed, hampering factor is time that no longer. So, student’s task was good enough for SMP level.Keyword : Extracurricular of Batik Work